ANALISIS POLA PERTUMBUHAN SUBSEKTOR PERTANIAN UNGGULAN KABUPATEN OKU TIMUR (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2015)
This study aims to determine the seed sub-sector of the agricultural sector and agriculture sector growth patterns featured in OKU District East by analyzing secondary data (time series) last 5 years (2008-2012). Data processing method in this study LQ (Location Quotient), DLQ (Dynamic Location Quotient) and Klassen Typologi of results were obtained: (1) sub-sector of food crops and plantation crops are seed subsector. Results of analysis DLQ plantation crops, forestry and food crops will be superior. (2) plantation and forestry sub-sectors including fast growing subsector. While the food crops sub-sector including advanced but depressed, while livestock and fisheries sub-sectors including relative and left behind